Virtual Impedance-based Decentralized Power Sharing Control of an Islanded AC Microgrid - Pathan, E.; Khan, M. H.; Arshad, H.; Aslam, M. K.; Jahangir, D.; Asad, M.; Rabani, M. I. (Engineering, Technology & Applied Science Research, 2021)
The future of power systems depends on the microgrid (MG) which includes distribution generators utilizing Renewable Energy Resources (RERs) and storage facilities. Decentralized control techniques are more reliable and stable in comparison with centralized controlled techniques. In this paper, a decentralized control strategy is presented for an islanded AC MG system. The control strategy includes improved droop control and virtual impedance. Control strategy with PI controllers to control the voltage and current is implemented to two Voltage Source Inverter (VSI) distribution generation units connected in parallel through a Point of Common Coupling (PCC). Circulating current and power-sharing deviations caused by the mismatched line impedance were taken into account. The proposed control scheme was tested in MATLAB/Simulink. Power-sharing accuracy and circulating current suppression were obtained by implementing the proposed virtual impedance-based decentralized control strategy.